ChemInform Abstract: Development of Soft Magnetic Materials Prepared by Metal Injection Molding. Issue 48 (2nd December 2014) - Shang, Feng; Qiao, Bin; He, Yi‐Qiang
Abstract Review: emphasis on the preparation of Fe‐based soft magnetic materials; 12 refs.